BASIC EQUATION OF MOLECULAR-KINETIC THEORY - Berkinov Alisher Abdurashidovich (Bright Mind Publishing, 2025)
This article discusses the basic equation, rules, brief history, and concept of ideal gas of molecular kinetic theory.
Keywords: Matter, molecule, diffusion, molecular-kinetic theory, ideal gas, chaotic, electromagnetic nature.